Laboratory assessment of factors affecting soil clogging of soil aquifer treatment systems - Pavelic, Paul; Dillon, P.J.; Mucha, M.; Nakai, T.; Barry, K.E.; Bestland, E. (Elsevier, 2011)
In this study the effect of soil type, level of pre-treatment, ponding depth, temperature and sunlight on clogging of soil aquifer treatment (SAT) systems was evaluated over an eight week duration in constant temperature and glasshouse environments. Of the two soil types tested, the more permeable sand media clogged more than the loam, but still retained an order of magnitude higher absolute permeability. A 6- to 8-fold difference in hydraulic loading rates was observed between the four source water types tested (one potable water and three recycled waters), with improved water quality resulting in significantly higher infiltration. Infiltration rates for ponding depths of 30 cm and 50 cm were higher than 10 cm, although for 50 cm clogging rates were higher due to greater compaction of the clogging layer. Overall, physical clogging was more significant than other forms of clogging. Microbial clogging becomes increasingly important when the particulate concentrations in the source waters are reduced through pre-treatment and for finer textured soils due to the higher specific surface area of the media. Clogging by gas binding took place in the glasshouse but not in the lab, and mechanical clogging associated with particle rearrangement was evident in the sand media but not in the loam. These results offer insight into the soil, water quality and operating conditions needed to achieve viable SAT systems.